Regulation of the Deposit of Duty on The Acquisition of Land And Building Rights by Clients to Notaries in The Transfer of Land and Building Rights - Anak Agung Krisna Sumantri; I Nyoman Putu Budiartha; Ni Made Jaya Senastri (Jurnal Smart Hukum (JSH), 2026)
The regulation of BPHTB deposits by clients to notaries in the transfer of land and building rights is a crucial issue in Indonesian notarial, land, and local-tax law. This article analyses the normative position of notaries who receive client deposits for Duty on the Acquisition of Land and Building Rights (BPHTB) and the legal responsibility arising when the deposit is not used according to its intended purpose. This study applies normative legal research with statutory, conceptual, and case approaches. Legal materials are examined through grammatical, systematic, and teleological interpretation. The analysis shows that notaries have attributed authority to prepare authentic deeds, whereas receiving and managing BPHTB deposits is not expressly regulated in the Law on Notary Position, PPAT regulations, or local-tax rules. The regulatory silence creates legal uncertainty because the practice continues on the basis of trust and service efficiency. If deposited funds are misused or the transfer process is not completed, the notary may incur civil, administrative, ethical, and criminal liability. The article recommends limited regulation based on written authorization, fund segregation, transparent receipts, prompt tax payment, and enforceable professional sanctions